Power factor correction in power delivery systems with mutipulse nonlinear loads - D. E. Egorov; V. P. Dovgun; N. P. Boyarskaya; A. V. Jan; A. S. Slyusarev (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Мutipulse rectifiers are widely used as a nonlinear loads in industrial distribution systems. The advantage of mutipulse rectifiers is low harmonic emission and high power factor. However input currents of mutipulse rectifiers have a wide spectrum including characteristic and noncharacteristic harmonics. This has a negative impact on the power quality. Shunt capacitors are the simplest form of reactive power compensation in industrial power distribution systems. However power systems with nonlinear loads suffer from severe harmonic distortion due to the parallel resonance between capacitors and system inductance. Special compensating devices for reactive power compensation and correction of power system frequency response for resonances damping are necessary. METHODS. In this paper shunt compensating devices for power delivery systems with multipulse nonlinear loads are considered. Proposed devices are composed of 3-5 order parallel connected passive broadband filters. They provide power factor correction, voltage and current harmonics mitigation and resonance modes damping. A general broadband filter design procedure based on frequency and reactive power scaling of normalized filter parameters is developed. RESULTS. Characteristics of different compensating devices configurations using broadband passive filters are discussed. It is shown that broadband filtering devices enable compensation of fundamental frequency reactive power as well as mitigation of voltage harmonic level to values determined by Russian and international standards. Proposed devices have lower fundamental power losses in c omparing with known solutions. CONCLUSION. Proposed analytical design method is applicable to broadband filters of different orders.